Deletion of relA abrogates the capacity of Mycobacterium avium paratuberculosis to establish an infection in calves - Park, Kun Taek; Allen, Andrew J.; Barrington, George M.; Davis, William C. (Frontiers in Cellular and Infection Microbiology, 2014)
Previous comparative studies in goats revealed deletion of relA but not pknG abrogates the capacity of M. a. paratuberculosis (Map) to establish a persistent infection. The immune response elicited by the mutant cleared infection. The objective of the present study was to extend the studies in calves and compare the proliferative response elicited by the relA deletion mutant (ΔrelA) and Map using flow cytometry and quantitative reverse transcription real-time PCR (qRT-PCR). Six 3-day-old calves were divided into two groups. Three were vaccinated with ΔrelA and 3 inoculated with wild type Map. The calves were challenged with Map 1 month later and necropsied 3 months post challenge. Three untreated calves were used as uninfected controls. Examination of tissues revealed the ΔrelA mutant was immune eliminated. Bacterial load of Map was significantly reduced in the calves vaccinated with ΔrelA and challenged with Map in comparison with calves inoculated and challenged with Map. A vigorous CD4 memory T cell response was detected at necropsy in PBMC from both infected groups. CD8 positive NK cells proliferated in the presence and absence of antigen stimulation in both treated groups but not in the uninfected group. IFN-γ, IL17, and IL22 gene expression were up-regulated with an associated increase in their transcription factors, Tbet and RORC, in both treated groups. TGF-β, IL-10, and FoxP3 were not up-regulated, indicating no activation of regulatory T cells. The findings show that the immune response to ΔrelA is clearly different than the response to Map. Understanding the immunological basis for this difference should facilitate development of a vaccine that elicits sterile immunity.